Perbedaan Self Confidence pada Ibu Menyusui Bekerja dengan Ibu Tidak Bekerja untuk Menyusui Ekslusif Selama 6 Bulan - Simangunsong, Rini Marni Agustina; Lestari, Widia (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The problem with exclusive breastfeeding for breastfeeding mothers is the lack of breast milk coverage caused by the mother's lack of self-confidence. In working mothers, the lack of breast milk coverage is influenced by not being provided with expressing facilities, while in non-working mothers it is due to low knowledge and understanding regarding breastfeeding. The aim of this research is to determine the difference in self-confidence between working breastfeeding mothers and non-working breastfeeding mothers. This research is quantitative research using a comparative descriptive design. The research sample was breastfeeding mothers with babies aged 0-6 months, totaling 156 respondents using purposive sampling techniques. The results of this research show that the majority of mothers are 20-35 years old, the mother's baby is 5 months old, the mother's education is high academic/graduate level, family type is nuclear family, parity is primiparous. The self-confidence of working mothers is highest in the objective, rational and realistic aspects, while the self-confidence of non-working mothers is highest in the objective and self-confidence aspects. The results of the analysis using the chi-squer test obtained a p value of 0.000 <0.05. It can be concluded that there is a difference in self-confidence between working and non-working breastfeeding mothers in the Rejosari Health Center work area.